PEMETAAN DAERAH RAWAN BENCANA ABRASI SEBAGAI UPAYA MITIGASI BENCANA DI PANTAI KABUPATEN TAKALAR - Nasiah Nasiah (Jurnal Environmental Science, 2021)
ABSTRACT The beach is an important local role in supporting human life. Most of the population lives on the coast, so the beach is an unstable region. Beach instability caused by the phenomenon is influenced by sea and land. Beach lately many have problems like abarasi, sedimentation and salt water intrusion. Formulated into research questions are: 1) How is the distribution of disaster-prone areas in coastal erosion and sedimentation Takalar, 2) How mitigation erosion and sedimentation in Takalar Beach. The results showed that most of the beach Takalar experience abrasion. efforts that have been taken by the government and communities to mitigate erosion of building embankments / walls, gabion, and groin. Directed to the beach bergisik are goats and hibiscus plant footprint, beach structural walls or embankments is.